Exploring nurses' perceptions of antipsychotic medication side effects: a smallest space analysis. (2nd January 2017) - Morrison, P.; Stomski, N. J.; Meehan, T.
ABSTRACT: Objective : Mental health nurses play a central role in delivering health care to people with severe mental health problems. Since antipsychotic medication remains the principal treatment for severe mental health conditions, an integral element of this role involves monitoring the effectiveness of medication and resultant side effects. The objective of this study was to examine nurses' perceptions of the assessment of antipsychotic medication side effects. Methods : A questionnaire was developed and then disseminated to members of the Australian College of Mental Health Nurses. Quantitative data were analysed using Smallest Space Analysis (SSA). Qualitative data were grouped into themes and used to further delineate the regions identified through the SSA. Results : Questionnaires were returned by 152 respondents, of which 140 were included in the analysis. The SSA identified the following four regions: personal confidence in assessing side effects; system responsibilities and practices for assessing side effects; collective responsibility for assessing side effects; and beliefs about side effect assessments. Discussion : Four important areas were identified that may underpin the use of antipsychotic medication side effect assessment tools. These areas are probably closely interrelated and form part of a complex social health care setting.